MindManager for Dummies - Cameron, Hugh (Wiley Publishing, 2011)
The first book available on this fast-growing and highly regarded software package MindManager allows users to visually map their ideas and brainstorming sessions in order to better organize thoughts and put them into action. Exploring all there is to know about the MindManager product, including the Standard, Business, Enterprise, and handheld releases, this book walks readers through the process and techniques in using MindManager to communicate ideas. Hugh Cameron (Indianapolis, IN) heads Camtech, Inc., a clinical engineering company that extends its reach to incorporate a diverse group of projects. Roger Voight, PhD, is a certified project manager with more than 30 years of experience in software design, development, and software project management.